Evaluation of Trans Mamminasata Public Transportation Policy in Makassar City - Muhammad Yunus; Gazali Muh; Fitri Ismayanti Parawansa (Universitas Negeri Makassar, 2026)
This study evaluates the Trans Mamminasata public transportation policy in Makassar City, especially in corridor 5 in Makassar City, in the context of congestion challenges and urban accessibility efficiency. Although the purpose of transportation is to reduce the habit of using private vehicles, its implementation is plagued by service integration issues, limited geographical coverage due to subsidy reductions, and variations in user perceptions related to frequency, fleet comfort, and bus stop accessibility. This study uses a qualitative approach and William N. Dunn's evaluation framework (effectiveness, efficiency, adequacy, equity, responsiveness and accuracy) through observation, interviews with stakeholders and users, and document review. The results of the study were found to be quite effective in reducing congestion and efficient in scheduled operations. However, overall effectiveness and equitable accessibility are still hampered by the lack of multimodal integration. The responsiveness and policy accuracy aspects are quite adequate for congestion solutions, but infrastructure improvements are needed. From the findings, it is recommended to expand routes, reactivate inactive corridors, optimize pick-up gathering points and improve road and bus stop infrastructure, thus ushering in inclusivity and transportation accessibility in Makassar City.